EFFECT OF SUGAR CANE JUICE ON SLUMP VALUES, SETTING TIMES AND STRENGTH OF CONCRETE (Nigerian Journal of Technology, 2015)
The effect of sugar cane juice, (SCJ) on slump values, setting time and compressive strength of concrete cubes was investigated. A total of 32 concrete cubes of size 150x150x150mm with a mix ratio of 1:2:4 were cast with different percentages of unfermented sugar cane juice replacing some proportion of water in the concrete mix. Water/Sugar Cane Juice/cement ratio was held constant at 0.45. The concrete cubes were prepared by replacing water with SCJ in the following proportions 0, 25, 50 and 100%. The cubes were cured, tested and the physical properties of interest in this study were determined. The slump values of the concrete decreased from 40mm at 100: 0 (water:SCJ) to 18mm at 50:50 (water:SCJ) and to 0mm (collapse) at (0:100) (water :SCJ). The final setting time of concrete increased with increase in proportion of SCJ. The highest final setting time of 42 hours (considered excessive), occurred at 75:25 (water:SCJ) proportion. The compressive strength of the (water:SCJ) concrete decreased as the percentage of SCJ increased up to 25% SCJ. Thereafter, an increase in compressive strength was noticed up till 100% SCJ, with a maximum strength of 13.08N/mm2 occurring at 100% SCJ at 28 days. The early strength reduction is due to quick-setting of the concrete, at 25% SCJ, retardation commences and the strength of concrete increases. The study has been carried out at 0, 25, 50 and 100% replacement by weight of potable water with SCJ. A comparative study has been done between concrete made with potable water and those made with water/sugar cane juice.  http://dx.doi.org/10.4314/njt.v34i2.6